Platelet Protein-Related Abnormalities in Response to Acute Hypoglycemia in Type 2 Diabetes - Moin, Abu Saleh Md; Al-Qaissi, Ahmed; Sathyapalan, Thozhukat; Atkin, Stephen L.; Butler, Alexandra E. (Frontiers in Endocrinology, 2021)
Introduction: Patients with severe COVID-19 infections have coagulation abnormalities indicative of a hypercoagulable state, with thromboembolic complications and increased mortality. Platelets are recognized as mediators of inflammation, releasing proinflammatory and prothrombotic factors, and are hyperactivated in COVID-19 infected patients. Activated platelets have also been reported in type 2 diabetes (T2D) patients, putting these patients at higher risk for thromboembolic complications of COVID-19 infection. Methods: A case-control study of T2D (n=33) and control subjects (n=30) who underwent a hyperinsulinemic clamp to induce normoglycemia in T2D subjects: T2D: baseline glucose 7.5±0.3mmol/l (135.1±5.4mg/dl), reduced to 4.5±0.07mmol/l (81±1.2mg/dl) with 1-hour clamp; Controls: maintained at 5.1±0.1mmol/l (91.9±1.8mg/dl). Slow Off-rate Modified Aptamer (SOMA)-scan plasma protein measurement was used to determine a panel of platelet proteins. Results: Prothrombotic platelet proteins were elevated in T2D versus controls: platelet factor 4 (PF4, p<0.05); platelet glycoprotein VI (PGVI p<0.05); P-selectin (p<0.01) and plasminogen activator inhibitor I (PAII, p<0.01). In addition, the antithrombotic platelet-related proteins, plasmin (p<0.05) and heparin cofactor II (HCFII, p<0.05), were increased in T2D. Normalization of glucose in the T2D cohort had no effect on platelet protein levels. Conclusion: T2D patients have platelet hyperactivation, placing them at higher risk for thromboembolic events; however, this may not be exacerbated by glucose variability. Nonetheless, when infected with COVID-19, this risk may be compounded, and their propensity for a more severe COVID-19 disease course increased.